Pregnant Women’s Knowledge about Preventing Mother-to-Child HIV Transmission - Ulfa, Zakirah; Ardhia, Dara; Juwita, Ratna (Omni Nursing Journal, 2026)
Background: Human Immunodeficiency Virus (HIV) remains a major public health concern due to the risk of mother-to-child transmission during pregnancy, childbirth, and breastfeeding. Although the Prevention of Mother-to-Child Transmission of HIV (PMTCT) program has been integrated into antenatal care services in Banda Aceh City, HIV screening coverage among pregnant women remains limited. Objective: This study aimed to describe the knowledge level of pregnant women about preventing mother-to-child HIV transmission in public health centers in Banda Aceh, Indonesia. Methods: This study employed a quantitative descriptive research design using a cross-sectional approach. A total of 108 pregnant women were selected through simple random sampling. Data were collected using a structured questionnaire consisting of 18 items designed to assess pregnant women's knowledge of HIV and the prevention of mother-to-child HIV  transmission (PMTCT) program. The collected data were analysed using univariate analysis. Results: The majority of pregnant women had a good level of knowledge, accounting for 91 respondents (84.3%) and 17 (15.7%) respondents had a moderate level of knowledge. Conclusion: Most pregnant women attending public health centers in Banda Aceh demonstrate a good level of knowledge regarding the prevention of mother-to-child HIV transmission. However, a proportion of respondents still had only a moderate level of knowledge, indicating the need for continuous health education and strengthened antenatal counseling to improve awareness and support the successful implementation of PMTCT programs